2016
DOI: 10.1080/0092623x.2016.1207732
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Sexuality, and Relationships in Young Hispanic People

Abstract: This study explores the relation between gender differences and sexuality among young Hispanic people. Eight hundred and forty young people from Spain and Mexico filled out a self-administered questionnaire about sexuality (sexual experience, sexual orientation and sexual relationships) and gender (self-identification). Men in both Spain and Mexico more commonly report the practice of masturbation and vaginal sex, and are more likely to be unfaithful than women. Women in both countries report more steady partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…For this reason, this study evaluates the physical and social environment, specific sexual behaviors, the perception of the impact of confinement, and also how variables such as emotional state have been able to influence a greater or lesser impact on sexuality. Moreover, gender perspective has been included because it is a relevant factor of the experience of sexuality, as shown by different reviews (Petersen & Hyde, 2010) and articles in which gender differences are shown in different sexual behaviors or aspects, such as, for example, in the experience of the first sexual relationship (Reissing et al, 2012), in performing online sexual activities (Shaughnessy et al, 2011), in sexting (Baumgartner et al, 2014), in the use and acceptance of pornography (Willoughby et al, 2014), in sexual infidelities (Gil-Llario et al, 2017), in masturbation (Driemeyer et al, 2017), or in the use of sex toys (Davis & Hines, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, this study evaluates the physical and social environment, specific sexual behaviors, the perception of the impact of confinement, and also how variables such as emotional state have been able to influence a greater or lesser impact on sexuality. Moreover, gender perspective has been included because it is a relevant factor of the experience of sexuality, as shown by different reviews (Petersen & Hyde, 2010) and articles in which gender differences are shown in different sexual behaviors or aspects, such as, for example, in the experience of the first sexual relationship (Reissing et al, 2012), in performing online sexual activities (Shaughnessy et al, 2011), in sexting (Baumgartner et al, 2014), in the use and acceptance of pornography (Willoughby et al, 2014), in sexual infidelities (Gil-Llario et al, 2017), in masturbation (Driemeyer et al, 2017), or in the use of sex toys (Davis & Hines, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Gender, race, ethnicity, and cohabitation status play an essential role in human sexuality, in particular, in terms of sexual frequency. 17 , 18 , 19 However, contradictory findings appeared across some predictors, such as education and age. For instance, although much research has revealed a positive association between the level of education and sexual frequency, other reports have seen no relation.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, Hispanic women do not make up a homogeneous group and differences in terms of sexual orientation have been revealed (Deardorff, Tschann, & Flores, 2008;Gil-Llario, Giménez-García, Ballester-Arnal, Cárdenas-López, & Durán-Baca, 2017), as well as sexual attitudes (Ilabaca, Fuertes, & Orgaz, 2015) or sexual health behaviours based on gender inequality (Giménez-García et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, this study analyses the online sexual experience in Hispanic women from different countries (Mexico, Spain and Argentina). All of them share traditional values, such as marianismo (i.e., women as submissive to men) and machismo (i.e., men as autonomous and authoritarian) (Cianelli & Villegas, 2016), but not gender inequality as past literature has reported (Ballester et al, 2017;Gil-Llario et al, 2017). In particular, following the Gender Inequality Index (United Nations Development Programme, 2015), Spain shows a more equal position (15º position over 165) than Mexico (73º position over 165) and Argentina (77º position over 165).…”
Section: Introductionmentioning
confidence: 99%